THE IMPACT OF EFFECTIVE TIME MANAGEMENT ON BUSINESS PERFORMANCE IN THE NIGERIAN BANKING INDUSTRY - Akintayo, Dayo Idowu; Shadare Oluseyi Adetunji; Olaniyan, Toyin Solomon (Current Journal of Human Resource Management (CJHM), 2023)
Effective time management is crucial for the success of any organization, as it facilitates goal achievement, improves productivity, and enhances employee satisfaction. This study examines the impact of time management on business performance in the Nigerian banking industry. A survey research design was employed, and 477 respondents were selected using stratified sampling technique. Descriptive inferential statistics were used to analyze the data, and the findings revealed a significant contribution of time management to business performance. Additionally, the study found gender differences in perception of business performance based on time management practices. The study recommends that organizations should prioritize the specification of time bounds for task performance and promote compliance among employees. Effective time management allows for clarity in task performance, which leads to increased productivity and job satisfaction. As the banking industry serves as the backbone of modern business, the development of Nigeria largely depends on the banking system that considers time management as a contributing factor for business survival and economic growth. Thus, effective time management should be a priority for organizations seeking long-term profitability and high customer satisfaction.